The effects of Ultraviolet-B radiation on Antarctic sea-ice algae 1 - Ryan, KG; McMinn, A; Hegseth, EN; Davy, SK (Journal of Phycology, 2012)
The impacts of ultraviolet-B radiation (UVB) onpolar sea-ice algal communities have not yet beendemonstrated. We assess the impacts of UV onthese communities using both laboratory experimentson algal isolates and by modification of thein situ spectral distribution of the under-ice irradiance.In the latter experiment, filters were attachedto the upper surface of the ice so that the algaewere exposed in situ to treatments of ambient levelsof PAR and UV radiation, ambient radiation minusUVB, and ambient radiation minus all UV. After16 d, significant increases in chl a and cell numberswere recorded for all treatments, but there were nosignificant differences among the different treatments.Bottom-ice algae exposed in vitro were considerablyless tolerant to UVB than those in situ, butthis tolerance improved when algae were retainedwithin a solid block of ice. In addition, algaeextracted from brine channels in the upper meterof sea ice and exposed to PAR and UVB in the laboratorywere much more tolerant of high UVB dosesthan were any bottom-ice isolates. This finding indicatesthat brine algae may be better adapted to highPAR and UVB than are bottom-ice algae. The dataindicate that the impact of increased levels of UVBresulting from springtime ozone depletion on Antarcticbottom-ice communities is likely to be minimal.These algae are likely protected by strong UVBattenuation by the overlying ice and snow, by otherinorganic and organic substances in the ice matrix,and by algal cells closer to the surface.